Three’s Company: Understanding Communication Channels in Three-way Distributed Collaboration - Tang, Anthony; Pahud, Michel; Inkpen, Kori; Benko, Hrvoje; Tang, John; Buxton, Bill (CSCW '10, Conference on Computer Supported Cooperative Work, 2010)
We explore the design of a system for three-way collaboration over a shared visual workspace, specifically in how to support three channels of communication: person, reference, and task-space. In two studies, we explore the implications of extending designs intended for dyadic collaboration to three-person groups, and the role of each communication channel. Our studies illustrate the utility of multiple configurations of users around a distributed workspace, and explore the subtleties of traditional notions of identity, awareness, spatial metaphor, and corporeal embodiments as they relate to three-way collaboration.